1996
DOI: 10.1016/0921-4488(95)00776-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of cold carcass weight and fat depth measurements to predict carcass composition of Rasa Aragonesa lambs

Abstract: A total of 22 measurements of fat depth, taken along the 13th rib, 5-6th lumbar vertebra, 3-4th sacrum vertebra, and the 2nd, 2-3rd, 3rd, 3-4th, 4th. 4-5th stemebra of the breast bone, were taken on intact carcasses with a sharpened steel rule, and related to the carcass composition of 18 Rasa Aragonesa lambs. The objective was to study the accuracy of these different measurements for predicting carcass composition and possible value, in the process of carcass grading or classification of 'Temasco' Aragdn lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Although the very thin subcutaneous fat layer of light lambs used in the present study limited the potential of ultrasound to provide accurate measurements (Teixeira et al, 2006), it is probably the narrow range of BW that was responsible for these results. This would be in accordance with the results of Delfa et al (1995Delfa et al ( , 1996a, who used in vivo and carcass ultrasound on the same kinds of animals, with carcasses weighing between 8.5 and 11.5 kg. Delfa et al (2007) used lambs slaughtered at 22.4 kg, with a SD of 0.96, but despite the narrower range of BW than was considered in our study, these authors achieved R 2 of 0.70, 0.81, and 0.51 for muscle, subcutaneous fat, and bone, respectively.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Although the very thin subcutaneous fat layer of light lambs used in the present study limited the potential of ultrasound to provide accurate measurements (Teixeira et al, 2006), it is probably the narrow range of BW that was responsible for these results. This would be in accordance with the results of Delfa et al (1995Delfa et al ( , 1996a, who used in vivo and carcass ultrasound on the same kinds of animals, with carcasses weighing between 8.5 and 11.5 kg. Delfa et al (2007) used lambs slaughtered at 22.4 kg, with a SD of 0.96, but despite the narrower range of BW than was considered in our study, these authors achieved R 2 of 0.70, 0.81, and 0.51 for muscle, subcutaneous fat, and bone, respectively.…”
supporting
confidence: 74%
“…These measurements were made at 2 and 4 cm from the nearest end of the LM to the backbone (Delfa et al, 1996a), and at 1/3 of the LM width (Delfa et al, 2007; Figure 1). With the probe parallel (Figure 2) to the dorsal midline, the following were also measured: LM depth (US_MDP); skin thickness + subcutaneous fat thickness + interfaces (US_FDP); subcutaneous fat thickness + interfaces (US_FDGIP); subcutaneous fat thickness (US_FDGP); and skin thickness (US_SKP) at 1/3 of the total length of the transverse apophysis from the dorsal midline (Delfa, 2004).…”
Section: Ultrasound Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raji et al (2009) reported that the relationship between live body measurement for estimation of carcass component in vivo depends on the correlation between them, these observation was noticed here with higher correlation existing between body weight and carcass components (.906, .950 and .786) with carcass weight , breast weight and thigh weight respectively. Several authors, (Sehested 1986;Teixeira et al, 2006;Wood and Maefie, 1980;Delfa et al, 1996) observed that multiple regression models developed to predict lean meat weight are dominated by live weight or carcass weight . In the present findings, prediction of both the carcass weight and breast weight seems to have been mainly influenced singly by the body weight 82 and 90.2%…”
Section: Resultsmentioning
confidence: 99%
“…Kidney and pelvic fats from the two halves were removed and weighed to obtain the contents of kidney knob and channel fat (KKCF). The subcutaneous fat thickness (C) was measured with a calliper at 4 cm from the spinal column on the level of 13th rib (Delfa et al, 1996).…”
Section: Slaughter Procedure Carcass Measurements and Dissectionsmentioning
confidence: 99%